تأثير كتابة اليوميات الترقية مهارة كتابة الإنشاء - Syaifuddin, Muhammad; Wafa, Ali; Zahro, Rizka Umami; Alfiana, Nurul Laili (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Teaching world languages, especially Arabic, has language skills steps that are well known among linguists. Namely listening skills, speaking skills, reading skills, and writing skills and one of them is writing skills. Students must understand and learn it. The purpose of this study was to determine the efficiency of writing skills insya' or maharah al-kitabah and to find out the application of diary writing to maharah al-kitabah in Arabic language learning. The research method that the researcher uses is a scientific quantitative method in obtaining knowledge by using data or numbers. Researchers believe that keeping a diary can simplify the process. Teaching Arabic to students, especially in writing skills. According to researchers, a diary is a record of events in a person's personal experience and is considered important to him. And write in a book or notebook in order according to the order of the day or time. This diary writing process has an impact on improving students' essay writing skills because by writing a diary, you can help students develop ideas. them when writing, and also to practice Arabic grammar mastery and to increase or increase students' vocabulary.